2013
DOI: 10.1093/aje/kwt227
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and the Risk of Colorectal Adenomas: Black Women's Health Study

Abstract: Evidence for the association of type 2 diabetes mellitus (DM) with colorectal neoplasms is contradictory, and African Americans have been underrepresented in the studies published to date. In a nested case-control study (1995-2009), we examined DM and insulin therapy as risk factors for colorectal adenomas in African American women enrolled in the ongoing Black Women's Health Study. From women reporting ever having undergone a gastrointestinal endoscopy, 917 cases of colorectal adenoma were compared with 2,751… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Of those remaining articles, we excluded studies that : (1) reported the data of adenoma recurrence were excluded [ 31 , 32 ], (2) did not reported the RRs of getting CRA separately but mixed CRC and CRA patients [ 31 ], and (3) discussed the relationship between metformin [ 33 ] or insulin use [ 34 ] and CRA. We identified 17 studies that met all of our criteria [ 13 20 , 35 – 44 ], including four conference abstracts [ 36 , 37 , 43 , 44 ]. Figure 1 provides a flow chart of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those remaining articles, we excluded studies that : (1) reported the data of adenoma recurrence were excluded [ 31 , 32 ], (2) did not reported the RRs of getting CRA separately but mixed CRC and CRA patients [ 31 ], and (3) discussed the relationship between metformin [ 33 ] or insulin use [ 34 ] and CRA. We identified 17 studies that met all of our criteria [ 13 20 , 35 – 44 ], including four conference abstracts [ 36 , 37 , 43 , 44 ]. Figure 1 provides a flow chart of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…However, the association between T2DM and the risk of CRA risk has not yet been fully established. Some researchers asserted that there were no overall associations between T2DM and CRA risk [ 13 16 ], while others reported a higher risk [ 17 20 ]. To further examine these findings and provide evidence of association between T2DM and risk of CRA risk, we performed a meta-analysis about T2DM on the risk of CRA.…”
Section: Introductionmentioning
confidence: 99%
“…1) (References in Table 1: Kim et al, 2015[ 22 ]; Kanadiya et al, 2013[ 20 ]; Cho et al, 2014[ 6 ]; Jain et al, 2016[ 18 ]; Eddi et al, 2012[ 12 ]; Lewis et al, 2007[ 26 ]; Chung et al, 2008[ 7 ]; Lee et al, 2012[ 25 ]; Marks et al, 2015[ 29 ]; Han et al, 2017[ 16 ]; Shin et al, 2013[ 32 ]) and 2 (Tab. 2) (References in Table 2: Chung et al, 2008[ 7 ]; Jain et al, 2016[ 18 ]; Eddi et al, 2012[ 12 ]; Dash et al, 2013[ 9 ]; Wong et al, 2012[ 39 ]). Of the 11 studies presented based on metformin treatment (Table 1 (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…The summary ORs of meta-analysis (OR=1.43, 95 % CI=1.15 to 1.78; P=0.002) revealed that there was a significant positive association between colorectal adenoma incidence and insulin intake between T2DM patients according to the 5 including studies (Figure 5 (Fig. 5) ; References in Figure 5: Chung et al, 2008[ 7 ]; Dash et al, 2013[ 9 ]; Jain et al, 2016[ 18 ]; Wong et al, 2012[ 39 ]; Eddi et al, 2012[ 12 ]). Then the insulin recipient patients had a risk of colorectal adenoma compared with those who did not.…”
Section: Resultsmentioning
confidence: 99%
“…Large prospective studies have demonstrated that DM is associated with an increased risk of colon cancer in people investigated[211-217]. Many meta-analysis studies also support a correlation between DM and increased risk of colon cancer[142-144,218-222].…”
Section: Clinical Consequences Of Diabetes-induced Changes In Intestimentioning
confidence: 99%